Recurrent Subdural Hematoma: A Case Report of Diagnostic Pitfall of Spontaneous Intracranial Hypotension and Successful Management With Targeted Epidural Blood Patch - Lili Chen; Guangyu Ying; Yucong Peng (Clinical Case Reports, 2025)
ABSTRACT Spontaneous intracranial hypotension should be considered in subdural hematoma cases without cerebral trauma or underlying disease, particularly among non‐elderly patients. Targeted epidural blood patch is recommended as a first‐line intervention prior to surgical management in cases of spontaneous intracranial hypotension‐induced subdural hematoma.